Changing Trends of Migration in Nepal (Rural Development Journal, 2024)
This paper aims at analyzing the changing trends of migration that have turned the world into a global village. The study focuses on how migration has affected all aspects of life including social, economic and demographic; and how it is affected by different factors like spatial variation in labour supply and demand, determined by economic concepts guided by wage differences, geographical opportunities and constraints. In the past, migration was limited to Tibet for trade and India for labour and trade. Later, as Lahure and British Gorkhali, they moved to Pakistan and India to serve as army. The major findings of this study shows that the top destination for the migrants who aspire for better survival are Malaysia, GCC countries remained the destination for economic reasons with moderate education level and the developed countries became the destination for high economic class step there for accomplishing their further study. The ratio of Male and female migrants has not only vast differences but also their prioritized destination also differs due to the kind of work they chose. Nepalese labour migration was badly affected by the COVID-19 pandemic due to restriction despite having labour approvals. Later many new destinations have been opened with options of work type. This article is mainly based on secondary data collected from different articles published in journals related to migration, regular reports published by CBS, NLMR, IOM and others.